"I Am Administering Medication—Please Do Not Interrupt Me": Red Tabards Preventing Interruptions as Perceived by Surgical Patients. Issue 1 (March 2019) - Palese, Alvisa; Ferro, Marcello; Pascolo, Marika; Dante, Angelo; Vecchiato, Sara
Abstract : Introduction: The recent introduction of red tabards aimed at avoiding interruptions during medication rounds has generated scientific and media debate, which is still ongoing. The principal aim of this study was to evaluate patients' perceptions of 3 different red tabards; the secondary aim was to explore individual factors associated with the negative perceptions that emerged. Methods: Eligible patients had to be admitted to the selected general surgical department and give written informed consent. A total of 104 patients were interviewed. Three real-sized red tabards, made with laminated paper and displaying different messages, were shown over 3 days to each patient involved. Results: Despite displaying different messages, from asking everyone not to disturb to allowing only patients to interrupt, patients perceived the tabards as directed at themselves. A different risk of preventing patients from communicating urgent needs emerged. The first tabard I am administering medication—Please do not interrupt me was most at risk to inhibit the patient. A negative impact was reported by 44 patients (42.3%) for the first tabard, 50 (48.0%) for the second tabard, and 40 (38.4%) for the third. In the logistic regression, only 2 independent factors were significantly associated with the negative perception of the message reported on the tabards: a positive attitude to interrupting nurses and receiving medication during their time in hospital. However, the variance explained by these factors ranges from 9.4% to 18.3%. Conclusions: On the basis of the findings that emerged, the adoption of the tabards should be evaluated considering the benefits already documented, and the potential negative effects that emerged on patients, which may be influenced by cultural and linguistic aspects. Wearing the tabard with the message reported on the back, directed to the staff and not the patients, may have less negative effects on patients; in addition, using a different color not to alarm the patients may be useful. In addition, comparing the red tabard effects with other strategies introduced to deal with avoidable interruptions (e.g., "no interruption zone") to gain a comprehensive picture regarding benefits/harm is also important.